ADVOKASI MELALUI MUSIK: STUDI KASUS LAGU "WE WILL NOT GO DOWN" DALAM GERAKAN KEBEBASAN GAZA - Fuad Reza Pahlevi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research examines the role of the song "We Will Not Go Down" in the advocacy of the Gaza freedom movement. This song, created by Michael Heart, has become a symbol of resistance and solidarity for the people of Gaza and has received international attention. This song was released in 2009 and is a protest song that describes the suffering of the Palestinian people due to the prolonged conflict with Israel. The lyrics call for steadfastness and determination not to give up in the face of the Israeli occupation forces and military aggression. The method used for this study is qualitative research and literature study. This study explores how music can be an effective advocacy tool in the context of conflict and oppression. Based on the theory put forward by Notoadmodjo in 2003, the concept of advocacy can be understood as a systematic approach to individuals or groups who are considered to have significant capability and influence in supporting the success of a particular program or activity. The research results show that the lyrics of this song succeeded in conveying a strong humanitarian message, arousing emotions and encouraging global solidarity action. These findings emphasize the importance of music as a medium of communication and gathering support in social and political movements